The Predictive Role of Low Spatial Frequencies in Automatic Face Processing: A Visual Mismatch Negativity Investigation - Lacroix, Adeline; Harquel, Sylvain; Mermillod, Martial; Vercueil, Laurent; Alleysson, David; Dutheil, Frédéric; Kovarski, Klara; Gomot, Marie (Frontiers in Human Neuroscience, 2022)
Visual processing is thought to be coarse-to-fine. According to Bar et al. (2006) low spatial frequencies (LSF), conveying coarse information, would be processed early to generate predictions. These LSF-based predictions would facilitate the further integration of high spatial frequencies (HSF), conveying fine details. The predictive role of LSF might be crucial in human automatic face processing, where high performance could be explained by an accurate selection of clues in early processing. In the present study, we used a visual Mismatch Negativity (vMMN) paradigm by presenting an unfiltered face as standard stimuli, and the same face filtered in LSF or HSF as deviant, to investigate the respective role of LSF and HSF during automatic face processing. If LSF are critical for predictions, we hypothesize that LSF deviants would elicited less prediction error than HSF deviants. Results show that both LSF and HSF deviants elicited a mismatch response compared with their equivalent in an equiprobable sequence. However, in line with our hypothesis, LSF deviants elicit significantly reduced mismatch responses (i.e., less prediction errors) compared to HSF deviants, particularly at later stages. The difference in mismatch between HSF and LSF conditions involves posterior areas and fusiform gyrus. Overall, our findings suggest a predictive role of LSF in automatic face processing and a critical involvement of HSF in the fusiform during the conscious detection of changes in faces.